Treatment of Laundry Wastewater Using Different Coagulants: Alum and HCA - Nisa', Syadzadhiya Qothrunada Zakiyayasin; Novembrianto , Rizka; Rosariawari, Firra; Rhomadhoni, Muslikha Nourma; Azzahra, Maulayya Fatimah (Future Science, 2023)
The wastewater from industrial laundries has a high quantity of contaminants from the washing process, as well as chemical additives. The current study assessed the efficacy of the coagulation/occultation/sedimentation (C/F/S) method to treat laundry wastewater in relation to physicochemical parameters of water quality with the goal of treating this type of wastewater. For this purpose, an experimental design was applied to the C/F/S step using the addition of coagulant Alum, coagulant Alum plus flocculant Superfloc, and coagulant HCA. Alum coagulant has removal efficiency of 52% for COD and 37% for phosphate. The use of alum coagulant and Superfloc flocculant produces COD removal efficiency of 60% and phosphate removal efficiency of 58%. The use of HCA coagulant shows a removal efficiency of 64% for COD and 78% for phosphate. This shows that using more HCA coagulant is more effective than using alum coagulant and Superfloc flocculant in laundry wastewater treatment.